CREATING NEW METHODS OF TEACHING FOR THE LESSONS - KHASANOVA ZAROFAT KENJAYEVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
The article deals with the problems of developing the technological competence of future teachers. It contains definitions of the concepts of competence and technological competence, provides an overview of the history of entry into education and the current level of relevance. The content of the work of the specialist, the level of mechanization and automation, its features, that is the level of organization and conditions, that is sanitaryhygienic, economic, social and safety conditions - fully reflects the form, method and procedure of connection highlighted.